2016
DOI: 10.1208/s12248-016-9901-6
|View full text |Cite
|
Sign up to set email alerts
|

Reserpine Inhibit the JB6 P+ Cell Transformation Through Epigenetic Reactivation of Nrf2-Mediated Anti-oxidative Stress Pathway

Abstract: Abstract. Nuclear factor erythroid-2 related factor 2 (Nrf2) is a crucial transcription factor that regulates the expression of defensive antioxidants and detoxification enzymes in cells. In a previous study, we showed that expression of the Nrf2 gene is regulated by an epigenetic modification. Rauvolfia verticillata, a traditional Chinese herbal medicine widely used in China, possesses anticancer and antioxidant effects. In this study, we investigated how Nrf2 is epigenetically regulated by reserpine, the mai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
11
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 26 publications
(15 citation statements)
references
References 67 publications
2
11
1
Order By: Relevance
“…Chronic administration (30 μΜ) of reserpine to C. elegans increased its lifespan by 31%, provided stress tolerance and delayed age-related decline in the mobility of the worm [ 91 ]. These results are further supported by another study, which suggests that reserpine exerted cancer-preventive properties by reactivating Nrf2 and inducing the expression of cytoprotective genes [ 128 ]. Although the use of reserpine as an anti-ageing factor is rather promising, according to Drugs.com (Drugs Information Database) the clinical use of reserpine as anti-psychotic and anti-hypertensive drug (0.1–0.5 mg orally daily) revealed numerous side-effects, such as respiratory, psychiatric and cardiovascular complications.…”
Section: Plant-derived Natural Compounds Specifically Modulating Nsupporting
confidence: 69%
“…Chronic administration (30 μΜ) of reserpine to C. elegans increased its lifespan by 31%, provided stress tolerance and delayed age-related decline in the mobility of the worm [ 91 ]. These results are further supported by another study, which suggests that reserpine exerted cancer-preventive properties by reactivating Nrf2 and inducing the expression of cytoprotective genes [ 128 ]. Although the use of reserpine as an anti-ageing factor is rather promising, according to Drugs.com (Drugs Information Database) the clinical use of reserpine as anti-psychotic and anti-hypertensive drug (0.1–0.5 mg orally daily) revealed numerous side-effects, such as respiratory, psychiatric and cardiovascular complications.…”
Section: Plant-derived Natural Compounds Specifically Modulating Nsupporting
confidence: 69%
“…Radix Angelicae sinensis extract and Z-ligustlide significantly reduced the level of methylation of the first five CpGs that lead to an increase in Nrf2 expression [ 42 ]. Some compounds might alter DNA demethylation and epigenetically enhance Nrf2 expression in JB6 P+ cells, including apigenin [ 43 ] and reserpine [ 44 ]. These reported indicated that some chempreventive compounds could activate the silenced Nrf2 gene via DNA demethylation.…”
Section: Discussionmentioning
confidence: 99%
“…Studies have demonstrated that DNA demethylation and histone (de)acetylation can trigger or increase Nrf2 expression. Natural compounds derived from plants (such as sulforaphane, corosolic acid, taxifolin, reserpine, quercetin, Z-ligustilide and curcumin) and marine constituents (fucoxanthin) have been shown to activate Nrf2 signaling through epigenetic regulation ( Khor et al, 2011 ; Su et al, 2013 ; Liu et al, 2015 ; Hong et al, 2016 ; Muta et al, 2016 ; Kuang et al, 2017 ; Jie et al, 2018 ; Yang et al, 2018c ; Zhao F. et al, 2018 ). Quercetin, a natural flavonoid, significantly inhibited nickel-induced inflammation in mouse liver by decreasing Nrf2 DNA methylation and inhibiting the p38 MAPK signaling pathway ( Liu et al, 2015 ).…”
Section: Molecular Mechanisms Of Cardioprotective Natural Products Tamentioning
confidence: 99%